# Help Using Cramer's rule to solve system of equations

• Jul 4th 2010, 04:43 PM
seanP
Help Using Cramer's rule to solve system of equations
here's the matrix for it:

| 2 0 -5 | | -1|
|-2 1 3 | | 6|
| 0 -1 6 | |-1|

Underneath is what i have worked out for it, but the values didn't work when i plugged them into the equations. I'm not sure what I've done wrong. I went over it and couldn't find anything. Any help is appreciated!

D=
| 2 0 -5 |
|-2 1 3 | = 2(1*6 – 3*-1) – 0(-2*6 – 3*0) + -5(-2*-1 – 1*0)
| 0 -1 6 | = 18 – 0 – 15 = 3 D=3

Dx1 =
| -1 0 -5 |
| 6 1 3 | = -1(1*6 – 3*-1) – 0(6*6 – 3*-1) + -5(6*-1 – 1*-1)
|-1 -1 6 | = -9 – 0 + 25 = 16 Dx1 = 16

Dx2 =
| 2 -1 -5 |
|-2 6 3 | = 2(6*6 – 3*-1) - -1(-2*6 – 3*0) + -5(-2*-1 – 6*0)
| 0 -1 6 | = 78 – 12 – 10 = 56 Dx2 = 56

Dx3 =
| 2 0 -1|
| -2 1 6 | = 2(1*-1 – 6*-1) – 0(-2*-1 – 6*0) + -1(-2*-1 – 1*0)
| 0 -1 -1 | = 10 – 0 – 2 = 8 Dx3 = 8

X1= Dx1/D
= 16/3

X2 = Dx2/D
= 56/3

X3 = Dx3/D
= 8/3
• Jul 4th 2010, 04:52 PM
seanP
nevermind...found the problem.
2x1 = 2, not 3 lol